MODEL MONITORING DAN IDENTIFIKASI PELANGGAR DI JALUR TRANSJAKARTA MENGGUNAKAN LIBRARY TESSERACT OCR PADA RASPBERRY PI 3 MODEL B - Abdul Haris; Efy Yosrita; Randi Adrika Putra (Jurnal Manajemen Informatika (JAMIKA), 2017)
TransJakarta Bus Lane is a special lane that is only passed by TransJakarta bus and is not allowed for other riders entering and passing the lane. But by reason of avoiding congestion, some riders break through the Transjakarta bus lane. This has distrubed Transjakarta bus travel schedule. Several attempts have been made by the government to prevent riders from entering TransJakarta route by installing 50 cm separator in several corridors, making Moveable concrete barriere and since Monday, 25 Noveber 2013 has been applied a maximum fine of Rp 500,000 for both the two- and four-wheeled vehicles or more, entering into a special line of TransJakarta bus or busway lane refers to article 287, Law No. 22 of 2009. The purpose of this study is to monitor in real time the rider who commits a violation or breaks through TransJakarta bus lane. The monitoring system is built in the form of hardware model consisting of Raspberry Pi 3 Model B, ultrasonic sensor HC-SR04, webcamera, and software in the form of website applications. Data processing vehicle license plate number using tesseract ocr library on raspberry. When the hardware model is turned on the ultrasonic sensor HC-SR04 detects the distance of the vehicle object, at a distance of â‰¤ 10 cm webcamera shoots the vehicle license plate model. Images taken by webcamera processed by raspberry using tesseract ocr library through threshold process so it can be read. The results is displayed on the website application so that it can known the identity of the violator.